Authentic Leadership, Power and Social Identities: A Call for Justice in Indian Higher Education System. (July 2020) - Sinha, Chetan
The current socio-political situation in India has gradually shifted the meaning of leader, power and identity in the Indian higher education system. Normalizing the diverse voices, oppression, concretizing the social categories and policing of education created a crisis of ethics. The majoritarian and populist leadership took the shape of an authentic leader, representing the identities of the groups who prejudice towards the minorities. The higher education systems such as universities have become a seat of monitoring and limiting dissenting voices and a neoliberal wave has taken over the whole system in the name of morality, nationalism and religious dominance. This article presents a critical analysis of leadership in the university settings and the way leadership processes are considered to be authentic and ethical in a cultural context.